1994
DOI: 10.1159/000244085
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Bolus Instillation: Effects of Different Doses on Blood Pressure and Cerebral Blood Flow Velocities

Abstract: Fifteen preterm infants suffering from respiratory distress syndrome were randomly allocated to receive either high-dose (200 mg/kg) or low-dose (100 mg/kg) surfactant treatment. Retreatments were done with the low dose. Blood pressure, blood gases and cerebral blood flow velocities were determined before and after 24 bolus instillations. With the high dose mean blood pressure and mean cerebral blood flow velocity dropped significantly. With the low dose only mean cerebral blood flow velocity decreased; the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Some studies reported that not all preterm infants experienced impaired autoregulation or pressure-passive cerebral circulation. 9,10 However, it should be noted that these studies involved a small number of infants with a higher birth weight and gestational age than those in our study. Furthermore, surfactant treatment was given prophylactically, which may mean that some infants were included who would not have developed RDS.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Some studies reported that not all preterm infants experienced impaired autoregulation or pressure-passive cerebral circulation. 9,10 However, it should be noted that these studies involved a small number of infants with a higher birth weight and gestational age than those in our study. Furthermore, surfactant treatment was given prophylactically, which may mean that some infants were included who would not have developed RDS.…”
Section: Discussionmentioning
confidence: 58%
“…Most of these studies demonstrated significant changes in blood pressure and CBFV within 5 minutes after surfactant administration and then returned to baseline levels within 20 to 30 minutes. [7][8][9][10][11] In human newborn infants, there are only two studies 12,13 using synthetic surfactant (colfoceril palmitate) (Exosurf; Glaxo Wellcome, Research Triange Park, NC), and these studies showed conflicting results with regard to CBFV changes. There is only one study using bovine natural surfactant that showed no significant changes in CBFV with surfactant administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations